Aspiration biopsy of mammary analogue secretory carcinoma of accessory parotid gland: Another diagnostic dilemma in matrix‐containing tumors of the salivary glands. Issue 1 (16th July 2012) - Levine, Pascale; Fried, Karen; Krevitt, Lane D.; Wang, Beverly; Wenig, Bruce M.
<x xml:space="preserve">Abstract</x> Mammary analogue secretory carcinoma (MASC) is a newly described rare salivary gland tumor, which shares morphologic features with acinic cell carcinoma, low‐grade cystadenocarcinoma, and secretory carcinoma of the breast. This is the first reported case of MASC of an accessory parotid gland detected by aspiration biopsy with radiologic and histologic correlation in a 34‐year‐old patient. Sonographically‐guided aspiration biopsy showed cytologic features mimicking those of low‐grade mucoepidermoid carcinoma, including sheets of bland epithelial cells, dissociated histiocytoid cells with intracytoplasmic mucinous material, and spindle cells lying in a web‐like matrix. Histologic sections showed a circumscribed tumor with microcystic spaces lined by bland uniform epithelial cells and containing secretory material. The tumor cells expressed mammaglobin and BRST‐2. The cytologic features, differential diagnosis, and pitfalls are discussed. The pathologic stage was pT1N0. The patient showed no evidence of disease at 1 year follow‐up. Diagn. Cytopathol. 2014;42:49–53. © 2012 Wiley Periodicals, Inc.